ANALISIS KESALAHAN PESERTA DIDIK KELAS X DALAM MENYELESAIKAN SOAL TRIGONOMETRI MENURUT TAHAPAN KASTOLAN DI SMAN 1 BONJOL - Dwi Fani Eriza (Jurnal Edukasi dan Penelitian Matematika, 2021)
This study aims to analyze and describe the types of errors committed learners in solving Trigonometry based on the stages of Kastolan. This type of research is qualitative deskripstif with the subject of the research is the 6 students of class X MIPA 1 SMAN 1 Bonjol. Data collection techniques in the form of a written test which are prepared in the form of the description (essay examination) as much as 9 point about, interview and documentation study. The technique of the analysis conducted in this research is Data Reduction, Data Display and Conclusion Drawing. From the results of the student error analysis, conceptual errors were obtained with an error percentage of 28.65% consisting of indicator 1 as much as 29.65% conceptual error, indicator 2 as much as 58.01% conceptual error and indicator 3 as much as 12.34% conceptual error; procedural error as much as 34.39% which consisting of indicator 1 as much as 43.11% procedural errors, indicator 2 48.86% procedural errors and indicator 3 as much as 7.95% procedural errors; technical errors are the most common mistakes made by students with a percentage of 36.96% with indicator 1 as much as 20.95% technical error, indicator 2 as much as 68.57% technical error and indicator 3 as much as 10.47% technical error. Keywords– Typesoof Castor Errors, Conceptual0Errors, Procedural0Errors, Technical0Erros, Trigonometry